2022
DOI: 10.3390/bioengineering9110694
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygen Transference on Protease Production by Rhodotorula mucilaginosa CBMAI 1528 in a Stirred Tank Bioreactor

Abstract: Microbial proteases, especially aspartic proteases, are an essential group of enzymes produced from different microorganisms. Microbial proteases have several applications, mainly in the food, beverage, cosmetic, and pharmaceutical industries, due to their efficiency in the processing and in the manufacturing stages. The yeast Rhodotorula mucilaginosa CBMAI 1528 was isolated from the Antarctic environment and was previously reported to have higher extracellular aspartic protease production. In addition, advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…R. colostri strains also showed no proteolytic activity in this study. Machado et al ( 2022 ) isolated the yeast strain R. mucilaginosa from the Antarctic continent, which synthesised proteases with an activity of 124.9 U mL −1 . Enzyme unit was defined as the amount of enzyme at which an increase in absorbance of 0.001 was found under the experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…R. colostri strains also showed no proteolytic activity in this study. Machado et al ( 2022 ) isolated the yeast strain R. mucilaginosa from the Antarctic continent, which synthesised proteases with an activity of 124.9 U mL −1 . Enzyme unit was defined as the amount of enzyme at which an increase in absorbance of 0.001 was found under the experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported earlier that the k L a values for protease production from Bacillus strains varied in the range of 0.01 to 0.055 s − 1 (Calik et al, 2000;2003). Another recent study reported that the values for increased protease production by Rhodotorula mucilaginosa ranges from 18 to 135 h − 1 with agitation ranging from 100 to 500 rpm and aeration ranging from 1.0 to 2.5 vvm (Machado et al, 2022). The DO concentration in the culture broth depends on the OTR from the gas to the liquid phase and also on the rate of its consumption by the microorganism, OUR.…”
Section: Mass and Oxygen Transfer Studiesmentioning
confidence: 93%
“…due to inadequate oxygen transfer (Calik et Agitation is reported to be more effective than aeration for enzyme production as high agitation generates bubbles that increase the gas-liquid interface area as well as the residence time in the culture medium causing a higher rate of DO (Teruasmaki et al, 2018). Shear stress due to oxygen supply through high aeration rate adversely affect the organism's morphology, physiology, and consequently, the biomass generation and enzyme production (Machado et al, 2022).…”
Section: Mass and Oxygen Transfer Studiesmentioning
confidence: 99%
See 1 more Smart Citation